1989
DOI: 10.1093/ajcn/50.5.970
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition during pregnancy: the effects of an educational intervention program in Greece

Abstract: An intervention program was undertaken to assess dietary habits and the impact of nutrition education among pregnant women in the rural county of Florina, northern Greece. Analysis of dietary habits, nutrient intake, hemoglobin, and serum vitamin concentrations in an intervention and control group indicated that the population was adequately nourished although nutrient intake was below recommended levels for pregnant women. Nutrition counseling was associated with improvements in dietary intake and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 18 publications
1
81
0
Order By: Relevance
“…56 There are surprisingly few intervention studies on the specific impact of maternal health education on perinatal and newborn outcomes. Kramer 57 evaluated the evidence, including that from an intervention trial in Greece, 58 of the potential benefit of maternal nutritional advice during pregnancy on several outcomes. Although an increase in energy and protein intake during pregnancy was notable, the overall impact on maternal, perinatal, and neonatal outcomes was unclear.…”
Section: Antenatal Interventionsmentioning
confidence: 99%
“…56 There are surprisingly few intervention studies on the specific impact of maternal health education on perinatal and newborn outcomes. Kramer 57 evaluated the evidence, including that from an intervention trial in Greece, 58 of the potential benefit of maternal nutritional advice during pregnancy on several outcomes. Although an increase in energy and protein intake during pregnancy was notable, the overall impact on maternal, perinatal, and neonatal outcomes was unclear.…”
Section: Antenatal Interventionsmentioning
confidence: 99%
“…Fallah et al and Kafatos et al found that education on nutrition and food consumption could cause a positive change to improve levels of the nutritional knowledge of pregnant females (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the limited evidence available highlights potential benefits associated with nutrition education as an intervention for improving Fe status in Indian (23,24) and other populations (25,26) . In fact, our approach of nutrition education was around a social action of live demonstration of Fe-rich recipes.…”
Section: Discussionmentioning
confidence: 99%